Correlation Between Echodefecography and 3-Dimensional Vaginal Ultrasonography in the Detection of Perineal Descent in Women With Constipation Symptoms. Issue 12 (December 2016) - Murad-Regadas, Sthela M.; Pinheiro Regadas, Francisco Sergio; Rodrigues, Lusmar V.; da Silva Vilarinho, Adjra; Buchen, Guilherme; Borges, Livia Olinda; Veras, Lara B.; da Cruz, Mariana Murad
Abstract : BACKGROUND: Defecography is an established method of evaluating dynamic anorectal dysfunction, but conventional defecography does not allow for visualization of anatomic structures. OBJECTIVE: The purpose of this study was to describe the use of dynamic 3-dimensional endovaginal ultrasonography for evaluating perineal descent in comparison with echodefecography (3-dimensional anorectal ultrasonography) and to study the relationship between perineal descent and symptoms and anatomic/functional abnormalities of the pelvic floor. DESIGN: This was a prospective study. SETTING: The study was conducted at a large university tertiary care hospital. PATIENTS: Consecutive female patients were eligible if they had pelvic floor dysfunction, obstructed defecation symptoms, and a score >6 on the Cleveland Clinic Florida Constipation Scale. INTERVENTIONS: Each patient underwent both echodefecography and dynamic 3-dimensional endovaginal ultrasonography to evaluate posterior pelvic floor dysfunction. MAIN OUTCOME MEASURES: Normal perineal descent was defined on echodefecography as puborectalis muscle displacement ⩽2.5 cm; excessive perineal descent was defined as displacement >2.5 cm. RESULTS: Of 61 women, 29 (48%) had normal perineal descent; 32 (52%) had excessive perineal descent. Endovaginal ultrasonography identified 27 of the 29 patients in the normal group as having anorectal junction displacement ⩽1 cm (mean = 0.6 cm; range, 0.1–1.0 cm) and a mean anorectal junction position of 0.6 cm (range, 0–2.3 cm) above the symphysis pubis during the Valsalva maneuver and correctly identified 30 of the 32 patients in the excessive perineal descent group. The κ statistic showed almost perfect agreement (κ = 0.86) between the 2 methods for categorization into the normal and excessive perineal descent groups. Perineal descent was not related to fecal or urinary incontinence or anatomic and functional factors (sphincter defects, pubovisceral muscle defects, levator hiatus area, grade II or III rectocele, intussusception, or anismus). LIMITATIONS: The study did not include a control group without symptoms. CONCLUSIONS: Three-dimensional endovaginal ultrasonography is a reliable technique for assessment of perineal descent. Using this technique, excessive perineal descent can be defined as displacement of the anorectal junction >1 cm and/or its position below the symphysis pubis on Valsalva maneuver.